Health Behaviors among High School Students in Baqubah City/Iraq - Awad , Azal Mohammed; Naji, Arkan B. (Iraqi National Journal of Nursing Specialties, 2024)
Objective(s): This study aims to assess the health behaviors among secondary school students and their associated age and socio-economic status in Baquba City / Diyala. Methods: A descriptive cross-sectional study conducted during the period from October 1st, 2022 to March 5th, 2023. The study sample consisted of 400 high school students who were selected on a simple random sample. The study instrument, a 49-item questionnaire was designed and adopted to assess health behaviors; and validated by experts and its reliability was achieved by a pilot study. Data were collected through interviews and analyzed by applying descriptive and inferential statistical analysis. Results: The results indicate that the health behavior profiles of high school students show several worrisome trends. Notably, 43% reported acceptable physical care behaviors, while 63.8% showed poor exercise habits. Sleep and rest were acceptable for 34.8% of students, and eating habits were acceptable for 44.3%. Additionally, 69% had poor medication management behaviors, and 71% reported poor smoking behaviors. Psychosocial health was acceptable for 44% of students. The study also identified age and family socioeconomic status as significant predictors of students’ health behaviors (p = 0.001). Conclusion: The study results indicate that health behaviors among secondary school students in Baquba City are below the ideal level, and that the students’ ages and economic status were predictors of improving their health behaviors. Recommendations: The study adds knowledge related to health education for all segments of society towards healthy behavior. Further studies are needed to explore strategies for adopting healthy behaviors among different school stages like school health policies and practices study, guide to community preventive services and striving to reduce youth violence everywhere.